2020
DOI: 10.1186/s13052-020-00832-5
|View full text |Cite
|
Sign up to set email alerts
|

Auxological and endocrinological features in internationally adopted children

Abstract: In internationally adopted children disorders of linear growth, puberty development, thyroid function, and bone metabolism are frequently reported. It is important that these children receive careful auxological and endocrinological evaluations and follow-up.Pediatricians and other healthcare providers should be aware that auxological and endocrinological problems are common in newly arrived international adoptees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…The closure of schools, the sudden disruption of extended social and family relationships, the change in daily habits and parental anxiety about financial and other problems may have affected children’s emotional stability and sense of security [ 33 ]. As yet there is little data on how children in all countries responded psychologically to the crisis but [ 34 ] the importance of psychological factors in precocious puberty has been reported in children migrating from developing to developed countries, primarily through international adoption [ 35 ]. It has been hypothesised that for adopted children who move from a deprived environment to a resource rich environment, environmental factors which slow or delay pubertal development are deactivated while factors which favour pubertal development are enhanced, triggering the onset of puberty [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The closure of schools, the sudden disruption of extended social and family relationships, the change in daily habits and parental anxiety about financial and other problems may have affected children’s emotional stability and sense of security [ 33 ]. As yet there is little data on how children in all countries responded psychologically to the crisis but [ 34 ] the importance of psychological factors in precocious puberty has been reported in children migrating from developing to developed countries, primarily through international adoption [ 35 ]. It has been hypothesised that for adopted children who move from a deprived environment to a resource rich environment, environmental factors which slow or delay pubertal development are deactivated while factors which favour pubertal development are enhanced, triggering the onset of puberty [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…As yet there is little data on how children in all countries responded psychologically to the crisis but [ 34 ] the importance of psychological factors in precocious puberty has been reported in children migrating from developing to developed countries, primarily through international adoption [ 35 ]. It has been hypothesised that for adopted children who move from a deprived environment to a resource rich environment, environmental factors which slow or delay pubertal development are deactivated while factors which favour pubertal development are enhanced, triggering the onset of puberty [ 35 ]. Genetic factors cannot fully explain the high incidence of precocious puberty in internationally adopted girls as their average menarcheal age is lower than the average menarcheal age both in their foster countries and in their countries of origin [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Closures of schools reduced physical activity, expanded sedantary activities and cause the increase of childhood obesity. Recent studies revealed that changes in lifestyles associated with COVID-19 lockdown caused the increase of obesity prevalence among children and adolescents [9,10].…”
Section: Covid-19 Pandemic and Pubertymentioning
confidence: 99%
“…The effects of psychological stress on the development of puberty are not clearly known. Stagi et al [9] reported the importance of psychological factors in precocious puberty in children migrating from developing to developed countries.…”
Section: Covid-19 Pandemic and Pubertymentioning
confidence: 99%